2007
DOI: 10.1007/978-3-540-74122-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Classification by Means of Orthographic and Broad Phonetic Transcriptions of Speech

Abstract: In this study we investigate whether a classification algorithm originally designed for authorship verification can be used to classify speakers according to their gender, age, regional background and level of education by investigating the lexical content and the pronunciation of their speech. Contrary to other speaker classification techniques, our algorithm does not base its decisions on direct measurements of the speech signal; rather it learns characteristic speech features of speaker classes by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Van Bael and Van Halteren (2007) investigated classification of groups of speakers on the basis of phonetic transcriptions and reported that classification based on pronunciation features performed poorly. The authors discussed several possible explanations for this finding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Van Bael and Van Halteren (2007) investigated classification of groups of speakers on the basis of phonetic transcriptions and reported that classification based on pronunciation features performed poorly. The authors discussed several possible explanations for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Van Bael and Van Halteren (2007), to study differences in the choice and reduction of words between individual speakers, we applied a classification algorithm, in which speech fragments are attributed to their speakers on the basis of lexical and pronunciation patterns. If classification results in high performance scores, this would indicate that speakers differ in their speech habits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations